IN THE CONTEXT OF CONTEMPORARY INDIAN ART-CONTEMPORARY ART: वर्तमान कालीन भारतीय कला-समकालीन कला के संदर्भ में - Kesarwani, Sachin (International Journal of Research -GRANTHAALAYAH, 2019)
English: The overall development of art is part of the historical, social process. The artist establishes new dimensions through innovative experiments. In present times, not only in India but in the whole world, experimentism can be clearly marked. As change is a continuous process that exists from time to time in which the prevailing beliefs go on being accepted by generations. But a thoughtful conscious community rejects those beliefs and leads the society towards a new direction and new values. This is where change starts, as fast as the meanings of life are changing, the art is changing as fast as possible. Hindi: कला का समग्र विकास ऐतिहासिक, सामाजिक प्रक्रिया का अंग है। कलाकार नित-नवीन प्रयोगों के माध्यम से नये आयाम स्थापित करता है। वर्तमान समय में भारत ही नहीं अपितु समस्त विश्व में प्रयोगधर्मिता को स्पष्ट रूप से चिन्हित किया जा सकता है। जैसा कि परिवर्तन एक निरन्तर प्रक्रिया है जो आदिकाल से आज तक विद्यमान है जिसमें प्रचलित मान्यताएं पीढ़ियों द्वारा स्वीकृत होती हुई आगे बढ़ती है। किन्तु एक विचारशील सजग समुदाय उन मान्यताओं को अस्वीकार करते हुए एक नवीन दिशा एवं नवीन मूल्यों की ओर समाज को ले जाता है। यहीं से परिवर्तन प्रारम्भ होता है जितनी तीव्रता से जीवन के अर्थ परिवर्तित हो रहे हैं उतनी ही तीव्रता से कला में परिवर्तन हो रहा है।